Meibomitis. Clinical cases - A. E. Sukhomlinov; V. I. Baranov; A. A. Kruchinina (Российский офтальмологический журнал)
Meibomitis (M) is an inflammation of the meibomian gland (MG) with the involvement of the surrounding tissue. One of the causes of M is an obstructed outflow of fat secretion, complicated by an accompanying infection. The authors propose a new algorithm for the treatment of M (complex conservative therapy, probing of the meibomian gland with an eyelash, and dissection) and offer a classification of meibomitis, which provides a better understanding of the various forms and stages of the disease. Practical application of the proposed treatment algorithm and the classification of M are illustrated by four clinical cases, which reveal the possible causes of M, unusual forms of its manifestation, and open new possibilities of eyelash probing of the meibomian gland.